PEMADAMAN JARINGAN DISTRIBUSI 20 kV GARDU INDUK SIMPANG HARU - Nurmiati Pasra; Syarif Hidayat; Enry Idil Fitrian (Sekolah Tinggi Teknik - PLN, 2015)
PT. PLN (Persero) is a company engaged in the field of electricity supply. PLN is required to distribute electrical energy reliably and in accordance with the level of quality of service that has been determined. Therefore, it is necessary to evaluate the extent outage with SAIDI (System Average Interruption Duration Index) and SAIFI (System Average Interruption Frequency Index). With SAIDI can be taken remedial measures subsystems, both components or equipment. whereas with SAIFI can be taken remedial measures to overcome burnout procedure and speed up the repair time. In this thesis will be discussed, the calcution of the level of reliability (SAIDI,SAIFI) and the power loss is not channeled by interference outages in PT PLN (Persero) Region substation feeder Simpang Haru Polamas 2015.